The geography of you and me - Smith, Jennifer E. 1980- (New York Little, Brown, 2014)
Sparks fly when sixteen-year-old Lucy Patterson and seventeen-year-old Owen Buckley meet on an elevator rendered useless by a New York City blackout. Soon after, the two teenagers leave the city, but as they travel farther away from each other geographically, they stay connected emotionally, in this story set over the course of one year--Provided by publisher.
KAL-3944, donated by Jowana B. Bueser
Keywords: Voyages and travels -- Juvenile fiction; Social classes -- Juvenile fiction; Electric power failures -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction